Territorial Functioning, Victimisation And Fear Of Crime: A Comparative Study Of High And Low Crime Rate Estates. - Abdullah, A.; Bahauddin, A; Mohamed, B.; Ahmad, A.G. (2004)
There is substantial empirical support that links territorial functioning with low crime and fear of crime in the residential setting. However, for the concept to be useful in preventing crime and fear of crime, it is important for it to operate in different crime contexts, especially in high crime areas, where the problem poses a major concern.